Use of cacti in the Meztitlan Ravine Biosphere Reserve, Hidalgo, Mexico - Jiménez, Adriana Fuentes; Sierra, Cecilia L. Jiménez (SITIENTIBUS série Ciências Biológicas, 2007)
This present study was carried out in order to know the importance and use of cactaceous in the semi-arid zone of the Meztitlan Ravine Biosphere Reserve. The region under study compassed the municipalities of Metztitlán, Metzquititlán and Eloxochitlán where xerophile scrub dominates. The study was carried out by the use of interviews. Sixty interviews were applied and 27 towns were visited. A total of 36 (51.4%) species of cactaceous was recorded of the 70 reported ones in the Reserve. These 36 species are wild but 11 (24% of the total) also is cultivated in the patios of the houses. Out of these species, 14 (28%) are used for serveral purposes. This study includes four new records for the state of Hidalgo: Opuntia auberi Pfeiff., O. dillenii (Ker-Gawl.) Haw., O. joconostle F.A.C. Weber ex- Diguet and Acanthocereus pentagonus Line. A total of eight uses was registered in the interviews: sweet, construction, medicinal, handicraft, food, forage, cosmetic and ornamental. The most frequent uses are medicinal (Myrtillocactus geometrizans), in food (M. geometrizans and Opuntia sp.), in forage (Opuntia sp. and Cylindropuntia imbricata), for handicraft (Opuntia sp., M. geometrizans and Isolatocereus dumortieri). Greenhouses located in the Reserve were also visited and interviews to the workers were carried out. Both the culture and production of cactuses is a form to use the flora and not to put it in risk in their natural environment. Around 14 cacti species from the zone have been cultivated at the greenhouses.